The media in shaping the general cultural competence of young students - Олексюк, Ольга (Educological discourse, 2013)
This article analyzes the current conceptual approaches to the nature, content and structure of the general cultural competence of schoolchildren. Тhe results of rapid diagnostic of general cultural competence of schoolchildren are represented as well as the motives of choice of sources media. Differences in the formation of general cultural competence of schoolchildren are discovered, and ways to overcome them are offered.